2022
DOI: 10.3390/su142215129
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Impact of Financial Literacy, Financial Self-Control, and Demographic Determinants on Individual Financial Performance and Behavior: An Insight from the Lebanese Crisis Period

Abstract: This study investigated the effects of financial literacy, financial self-control, and demographic determinants on individual financial performance and behavior during the Lebanese crisis period between 2019 and 2021. To the best of our knowledge, this may be the first study that compares the determinants of financial behavior for different generations, genders, marital statuses, and education and income levels. To do so, we conducted a comprehensive survey of 328 individuals and performed a logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Besides, consumers require adequate financial empowerment to make appropriate financial decisions (Nam, 2022). To this end, as Mawad et al (2022) suggest, policies should help young adults acquire skills in self-control as well as integrating financial knowledge into school curricula. In this regard, as Boto-García et al ( 2022) also advocate, financial socialization, understood as the exposure to financial concepts while growing up, becomes essential.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, consumers require adequate financial empowerment to make appropriate financial decisions (Nam, 2022). To this end, as Mawad et al (2022) suggest, policies should help young adults acquire skills in self-control as well as integrating financial knowledge into school curricula. In this regard, as Boto-García et al ( 2022) also advocate, financial socialization, understood as the exposure to financial concepts while growing up, becomes essential.…”
Section: Discussionmentioning
confidence: 99%
“…Such relevance stems from the fact that self-control is vital in many facets of our life and that many of our everyday decisions, including the loan repayment decision, include exercising self-control (Lian et al, 2017). Mawad et al (2022) conducted a study in Lebanon and determined that self-control had a positive impact on an individual's financial performance and behavior, particularly at highly educated levels. Bu et al, 2022, executed a study which showed that a self-control training program, including spending tracking, budgeting, and introspection about consumption choices, effectively reduced future online borrowing and delinquency charges.…”
Section: Self-controlmentioning
confidence: 99%
“…The data used for this paper is based on the collected data by Mawad, et al [9]. The sample survey included 328 participants (157 men and 171 women).…”
Section: Data Descriptionmentioning
confidence: 99%
“…The researcher focused on the effect of good financial behavior on the negative relationship between financial optimism and financial fragility. Few studies focus on the impact of financial literacy but we take the study a step further and consider the impact of financial behavior which may include other determinants such as financial self-control [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation